2000
DOI: 10.1161/01.cir.101.17.2022
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of the Cyclin-Dependent Kinase Inhibitors p27 Kip1 , p21 Cip1 , and p16 Ink4 on Vascular Smooth Muscle Cell Proliferation

Abstract: p27(Kip1) and p21(Cip1) are potent inhibitors of VSMC growth compared with p16(Ink4) because of their different molecular mechanisms of cyclin-dependent kinase inhibition in the G(1) phase of the cell cycle. These findings have important implications for our understanding of the pathophysiology of vascular proliferative diseases and for the development of molecular therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
168
1
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(189 citation statements)
references
References 14 publications
18
168
1
2
Order By: Relevance
“…Indeed, the cyclin-CDK complex plays a critical role in cell cycle regulation by controlling phase transition of cell cycle progression, in which cyclin is the regulatory unit and CDK is the catalytic component of the complex. 26,27 The present results revealed that the PPARδ agonist leads to increased ROS production at 15 and 120 min as compared with controls. Thus, we investigated the effects of ROS sensitive signals such as PKC, cPLA 2 and p38 MAPK.…”
Section: Discussionsupporting
confidence: 55%
“…Indeed, the cyclin-CDK complex plays a critical role in cell cycle regulation by controlling phase transition of cell cycle progression, in which cyclin is the regulatory unit and CDK is the catalytic component of the complex. 26,27 The present results revealed that the PPARδ agonist leads to increased ROS production at 15 and 120 min as compared with controls. Thus, we investigated the effects of ROS sensitive signals such as PKC, cPLA 2 and p38 MAPK.…”
Section: Discussionsupporting
confidence: 55%
“…Consistent with the view that CDKIs are major negative regulators of the cell cycle, overexpression of Cip/Kip family members (p21 Cip1 , p27 Kip1 ) blocks the G 1 exit in VSMC and other cell types (5,6). Data emerging from recent studies, however, suggest that CDKIs p21…”
mentioning
confidence: 58%
“…These findings provide an important mechanistic link between the induction of NOR1-dependent Skp2 expression in response to mitogenic signaling and downstream p27 protein abundance. Maintaining elevated p27 levels prevents neointima formation following vascular injury (10). Conversely, recent work by Wu et al (24) has outlined that Skp2 deficiency increases p27 protein levels and inhibits VSMC proliferation.…”
Section: Discussionmentioning
confidence: 97%
“…The rate-limiting component of this SCF complex is Skp2 (S phase kinase-associated protein 2) (7), which is induced by growth factors and responsible for substrate recognition and degradation of p27 (8,9). In vascular cells, overexpression of p27 inhibits neointima formation, whereas its deficiency accelerates atherosclerosis formation (10,11). Conversely, ectopic SKP2 expression decreases p27 levels in VSMC, induces VSMC proliferation, and promotes pathological neointima formation (12,13).…”
Section: Vascular Smooth Muscle Cells (Vsmc)mentioning
confidence: 99%